Endoscopic Drainage of an Odontogenic Pterygoid Muscle Abscess - Rickul Varshney; Faisal Zawawi; Marc A. Tewfik (Case Reports in Otolaryngology)
The infratemporal fossa (ITF) is a potential space bounded by bony structures that can be occupied by both benign and malignant tumors. It is also a potential area of abscess development, most commonly of dental origin. As with any abscess, the treatment of an ITF abscess is surgical drainage. We present a case of an ITF abscess involving the pterygoid muscles following dental extraction in a poorly controlled diabetic patient. The ITF was accessed with an endoscopic transseptal approach through the maxillary sinus to drain the abscess. This case of successful management supports the feasibility of the endoscopic approach in dealing with abscesses of the ITF.